Trade Openness, FDI and Exchange Rate Effects on Job Creation in South Africa's Tradable Sectors - Chama CHIPETA; Daniel Francois MEYER (Journal of Economics and Behavioral Studies, 2018)
Employment creation remains the pinnacle standard of sound social welfare and economic progress. It is a fundamental driver of economic development for any economy. However, such a pursuit faces tenacious challenges, especially amidst the growing global market integration. This study unravelled the effects of the underlying trade environment mechanisms such as trade openness, foreign direct investment(FDI) and the exchange rate on South Africa’s job creation efforts within the tradable sectors. The study employed a quantitative analysis and included time series explanatory variables of trade openness, netFDI flows and the real effective exchange rate. Employment series of both South Africa’s mining and manufacturing tradable sectors served as the dependent variables. The study made use of quarterly observations starting from 1995 to 2016. In doing so, various econometric methods were utilised. These included descriptive analyses, the standard Autoregressive Distributed Lag (ARDL) model, and the TodaYamamoto Granger Non-Causality test. Empirical ARDL results of employment in the individual mining sector, established no long-run and short-run relationships with trade openness, the real effective exchange rate and net-FDI. Employment in the manufacturing tradable sector presented significant and negative longrun relationships with trade openness, the real effective exchange rate and net-FDI. Meanwhile, the short-run findings exhibited significant and positive relationships between employment in the manufacturing tradable sector with trade openness, and significantly negative for net-FDI. However short-run results of manufacturing employment and the real effective exchange rate were not significant. Based on these results, South Africa’s mining sector seems unresponsive to mechanisms in the trade environment while these relationships are relatively dynamic in the manufacturing sector. Further recommendations were thus provided to improve these interrelationships in promoting job growth and its responsiveness to trade components.